A Deconstruction of Corporate Responsibility in Criminal Law - Reda Manthovani; Erni Mustikasari; Mukhlis; Naglaa Fathy El Dessouky (Jurnal Justice Dialectical, 2025)
The recognition of corporate crime as a form of criminal participation raises critical issues regarding the scope and classification of corporate criminal responsibility in Indonesia. Despite its significance, there is currently no rigid legal framework providing clear guidelines on this matter. This study aims to establish an ideal framework for corporate criminal liability by applying a taxonomic method to classify types of criminal participation. Employing a normative legal research design with a legislation-based approach, the study analyzes both primary and secondary legal materials through deductive reasoning. The findings highlight two main points. First, a legal deconstruction is necessary to comprehend corporate crime as an evolving form of criminal participation, taking into account traditional attribution methods, existing legal practices, and reforms proposed in the draft Indonesian Criminal Code. Second, two predominant models for understanding corporate liability emerge: one that considers corporate actors’ criminal participation as part of their organizational duties, and another that focuses on individual actors’ involvement within the corporate structure. The study concludes that a normative reconstruction and clear classification of corporate crimes are essential to provide legal certainty and uphold justice. This framework aims to provide clearer guidelines for attributing criminal liability in corporate contexts in Indonesia.